Development of Green Chemistry Physics Practical Worksheet Based on Case Method in Chemistry Education Study Program - Sanjaya; Andi Suharman; M. Hadeli; Made Sukaryawan; Diah Kartika Sari; Eka Ad'hiya; Dinda Safitri; Siska Silaen (Jurnal Penelitian Pendidikan IPA, 2024)
This development research aims to develop LKM green chemistry physics chemistry practical worksheet based on case method as supplementary teaching materials for students of the Chemical Education study program at Sriwijaya University using the 4STMD (Four Step Teaching Materials Development) method. The steps of the 4STMD method, namely the first stage is the selection stage, carried out by analyzing needs, curriculum and analyzing the material by looking for references in various sources. The second stage, namely the structuring stage, is carried out by adding or subtracting material and compiling the material. The third stage is the characterization stage, carried out by developing the results of material analysis. The fourth stage is the didactic reduction stage, but the researcher did not carry out the didactic reduction stage. Data collection techniques used in the form of interviews, pre-research questionnaires and validation questionnaires. In the material validation test, the validity of teaching materials was obtained based on the Aiken coefficient of 0.75 which was categorized as high. Based on these results, it shows that the development of LKM Green Chemistry Physics Chemistry Practical Worksheet Based on Case Method has met the valid criteria.